Uncoupling of growth plate maturation and bone formation in mice lacking both Schnurri-2 and Schnurri-3 - Jones, Dallas C. (National Academy of Sciences, 2010)
Formation and remodeling of the skeleton relies on precise temporal and spatial regulation of genes expressed in cartilage and bone cells. Debilitating diseases of the skeletal system occur when mutations arise that disrupt these intricate genetic regulatory programs. Here, we report that mice bearing parallel null mutations in the adapter proteins Schnurri2 (Shn2) and Schnurri3 (Shn3) exhibit defects in patterning of the axial skeleton during embryogenesis. Postnatally, these compound mutant mice develop a unique osteochondrodysplasia. The deletion of Shn2 and Shn3 impairs growth plate maturation during endochondral ossification but simultaneously results in massively elevated trabecular bone formation. Hence, growth plate maturation and bone formation can be uncoupled under certain circumstances. These unexpected findings demonstrate that both unique and redundant functions reside in the Schnurri protein family that are required for proper skeletal patterning and remodeling.